Solanezumab for the treatment of mild-to-moderate Alzheimer''s disease. (February 2012) - Imbimbo, Bruno P; Ottonello, Simone; Frisardi, Vincenza; Solfrizzi, Vincenzo; Greco, Antonio; Seripa, Davide; Pilotto, Alberto; Panza, Francesco
Solanezumab (LY2062430) is a humanized monoclonal antibody that binds to the central region of ββ-amyloid, a peptide believed to play a key role in the pathogenesis of Alzheimer''s disease (AD). Eli Lilly & Co is developing an intravenous formulation of solanezumab for the treatment of mild-to-moderate AD. Acute and subchronic treatment with solanezumab of transgenic mice attenuated or reversed memory deficits with no effects on incidence or severity of cerebral amyloid angiopathy-associated microhemorrhages, a severe side effect associated with bapineuzumab, another monoclonal antibody. Phase II studies in AD patients have shown a good safety profile with encouraging indications on cerebrospinal and plasma biomarkers. The drug is currently being investigated in Phase III trials. While there is a strong hope that solanezumab may represent the first effective passive vaccine for AD treatment, skepticism still exists on the ability of the drug to slow the rate of deterioration in patients with fully established disease.